Effects of a program of intense physical activity on the body composition of adolescents from Murcia - López Sánchez, G. F.; Nicolás López, J.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
Introduction and objectives: This paper focuses on studying the effects of a physical activity program on body composition of a group of schoolchildren. Method: This investigation involved 35 students (13 boys and 22 girls), aged between 12 and 15 years (average age 13.54 and standard deviation 0.98). The variables considered were: fat mass, BMI (Body Mass Index), WHR (Waist to Hip Ratio). The body composition analysis was performed using bioelectrical impedance through the body fat monitor Tanita BC 418-MA Segmental. Stadiometer HM - 250P Leicester and Seca 201circumference measuring tape were also used. The procedure was as follows: pre-test, intervention and post-test. The intervention consisted of 3 days per week of high-intensity physical activity, 15 minutes per day, during 12 weeks. Results: Data analysis was performed through SPSS 22 and significant improvements were obtained in fat mass and BMI (Sig <0.05). Conclusions: The physical activity program used in this study may be useful to improve fat mass and BMI in adolescents.